KETRAMPILAN GURU B. INGGRIS ALIYAH DALAM MEMBUKA DAN MENUTUP PELAJARAN - ., Sholikin (Inovasi: Jurnal Diklat Keagamaan, 2018)
Opening a lesson is a very important part of the overall learningactivity, as it will give a deep impression to the students in theirlearning, as well as closing, where teachers and students will get a fullpicture of what they have learned and what to prepare for the nextlesson. In this study. On this occasion researcher tried to elaborate ofhow teachers open and close lessons. This research uses a descriptivequali tati ve research, by using observati on as data col lectioninstrument. While the population and sample are the teachers ofEnglish MTs se East Java, amounting to 35 people. The resultsshowed that teachers in opening lessons for components; Linkingcurrent learning materials with previous learners’ experiences orlearning 45.7 % (moderate), Asking challenging questions. 68.5 %(High), Delivering the benefits of learning materials. 40 % (low),Demonstrate something rel ated to the theme. 68.5% (Hi gh),Delivering ability to be achieved by learners, 54,7 % (Medium), whileDeli ver acti vity plan for example, individual, group work, andobservation. 34.2 % (Low). To close the lesson for components :Reflect or make a summary by involving students 51.4 % (Medium),Give the last oral 51.4 % (Last) oral test, Collect the work as portfoliomaterial, 45.7 % (Medium).